Generation and characterization of three induced pluripotent stem cell lines for modeling coronary artery vasospasm - Ines Ross Tacco; Joseph Olshausen; Tse Yuan Chan; Naima Turbes; Ming-Yow Hung; Chi-Tai Yeh; Patricia K. Nguyen; Karim Sallam; Nazish Sayed; Ian Y. Chen (Stem Cell Research)
Coronary artery vasospasm (CAV) is characterized by transient constriction of epicardial coronary arteries leading to angina. Its disease mechanisms are multifactorial but has centered mostly on endothelial dysfunction and smooth muscle hyperreactivity. To facilitate the investigation of these mechanisms in cell culture, we generated and characterized three induced pluripotent stem cell (iPSC) lines from patients with CAV. These lines demonstrated normal morphology and karyotypes, robust expression of pluripotency markers, and ability for tri-lineage differentiation. Further differentiation of these cell lines into endothelial and smooth muscle cells will allow mechanistic investigation of their relative contributions to CAV in cell culture.